Sakambari in Blue Mimosa - Sharma, Bimala (Haimaprabha, 2025)
The paper concentrates on Sakambari in the novel Blue Mimosa (1965) written by Parijat. The paper tries to find answers of the set research questions: How does Sakambari’s character threatens conventional gender roles in Blue Mimosa, in what ways does Sakambari’s existential struggle contribute to the novel’s thematic depth, and how does Sakambari represent the societal restrictions imposed on women in Nepal ? Feminist and existentialist theories are the lenses to explore the novel and find answers to the afore mentioned questions. Blue Mimosa by Parijat is the primary text and secondary sources include other supporting materials available on the novel and theories. A qualitative research methodology is used to examine gender roles, existential encounters, and social constraints in Blue Mimosa. The study employs feminist theory to investigate Sakambari’s rebelliousness in contradiction of patriarchal rules and regulations and existentialist theory, drawn from Sartre and Camus to investigate about her quarantine and hunt for meaning. Simone de Beauvoir’s notion of The Second Sex’ is also employed to comprehend Sakambari’s position as ‘other’ in her own society. Feminist theory, existentialist theory and intersection of feminism and existentialism are the key lenses. Sakambari in Blue Mimosa includes the analytical section where Sakambari’s challenge to traditional gender roles, Sakambari’s existential struggle, and Sakambari as a representation of societal restrictions on women in Nepal are analyzed. The findings of this paper are defiance against gender norms, existential isolation and freedom, and critique of patriarchal oppression.